Genetic Improvement Program Data - Mengistu, Samuel; Mwanza, Yvonne; Malambo, Tom; Hamilton, Matthew (2025)
This deliverable includes family production data, harvest data, other data and reports from the GIP programs in Zambia and Malawi.